The Role of Legal Knowledge in Strengthening Consumer Protection and Access to Justice - M. Shidqon Prabowo (UNISSULA, 2025)
Consumers’ low level of legal awareness regarding their rights remains a significant factor contributing to their weak ability to seek protection when violations occur. Although consumer protection is firmly regulated under Law Number 8 of 1999 concerning Consumer Protection and its implementing regulations, many consumers still do not fully understand or exercise their rights. This study examines how consumers’ knowledge influences their awareness and behavior in utilizing legal protection mechanisms, as well as evaluates the effectiveness of existing regulations. Using a qualitative approach with a normative legal research method, primary data is derived from statutory provisions, while secondary data is collected through literature reviews of books, journals, academic articles, and legal documents. The findings indicate that consumers with higher levels of legal knowledge are more proactive in defending their rights through authorized institutions such as Community-Based Consumer Protection Organizations and Consumer Dispute Resolution Agency. In contrast, those with limited legal knowledge tend to be passive and view violations as common occurrences. Key challenges include low legal literacy, insufficient access to dispute resolution bodies, and inadequate dissemination of consumer protection regulations. To strengthen consumer protection, comprehensive legal education, improved institutional performance, and collaborative efforts among stakeholders are essential in enhancing public legal awareness and access to justice.